Lipid digestion of oil-in-water emulsions stabilized with low molecular weight surfactants. Issue 12 (8th November 2019) - Ng, Natalie; Chen, Peter X.; Ghazani, Saeed M.; Wright, Amanda J.; Marangoni, Alejandro; Goff, H. Douglas; Joye, Iris J.; Rogers, Michael A.
Abstract : Altering sn -fatty acid position of glycerol mono-oleate (GMO) from sn -1 to sn -2 decreases fatty acid bioaccessibility by 25.9% providing possible strategies to tailor lipemic responses of food emulsions. Abstract : Altering sn -fatty acid position of glycerol mono-oleate (GMO) from sn -1 to sn -2 decreases fatty acid bioaccessibility by 25.9% providing possible strategies to tailor lipemic responses of food emulsions. Lipid digestion kinetics and fatty acid bioaccessibility of monomodal O/W emulsions stabilized at their minimum surfactant concentration (0.5 < MSC > 0.7 (w/w)) were studied in the TNO Intestinal Model (TIM-1) gastrointestinal (GI) tract. No significant differences were observed between induction times nor rate constants when using 1-GMO and 1-GMS, Span 60, Tween 60 and Tween 80 as surfactants in O/W emulsions, as determined by fitting a three-parameter shifted logistic model to the cumulative bioaccessibility. Comparable trends were observed between area under the curve (AUC) of the absolute bioaccessibility and total overall bioaccessibility.